Pelatihan Membatik Sebagai Wujud Pengembangan SDM Dalam Upaya Melestarikan Kebudayaan Batik di Kelurahan Menanggal Surabaya - Thalita Alsa Dilla Putri; Virginia Mandasari; Ayundha Evanthi (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Indonesia is a multicultural country with various arts and cultures in it. It is the responsibility of all parties to maintain this cultural heritage so that it remains sustainable. One of the proud heritages of the Indonesian people is batik. Batik is a characteristic that has become the identity of the Indonesian people. The increasingly sophisticated technology has made many people lose interest in Indonesian arts and culture. The lack of participation of the younger generation in the preservation of batik culture has led to the decline in the existence of batik, especially written batik, among the community. One of the areas that tries to maintain the existence of batik culture is Menanggal Village with the establishment of Sanggar Batik Modern Menanggal, but the lack of human resources is an obstacle to the realization of batik preservation. In response to this, UPN